Evaluation and comparison of energy use efficiency among cucumber greenhouses - Behroozeh, Samira; Hayati, Dariush; Karami, Ezatollah; Nassiri, Seyed Mehdi; Rezaei-Moghaddam, Kurosh (Frontiers in Sustainable Food Systems, 2024)
Construction of agricultural greenhouses can be considered as one of the appropriate solutions to meet the growing food demands. However, high energy use in greenhouse productions on the one hand and energy limitation on the other hand are fundamental challenges facing mankind.The present study aims to measure and compare energy efficiency based on the components of energy use sustainability (Environmental Norms, Environmental Beliefs, Environmental Values, Technical Management, Technical Knowledge, Education Level, Greenhouse's Work Experience, Cost-Effectiveness and Educational -Extension Service) among greenhouse cucumber growers. The statistical population included cucumber production greenhouse owners in Kerman Province, Iran. Out of the total population, 356 cases were selected as a sample using two-stage cluster sampling method. The results showed that the average energy efficiency in the studied units was 0.72 (out of 1), so that 21 and 335 greenhouses used energy efficient and inefficient, respectively. According to the components of energy use sustainability, a significant difference was observed between efficient and inefficient greenhouses, so that the energy efficient greenhouses have a high level of related components. It is suggested that the decisionmakers, stakeholders, and active policy makers in the field of greenhouse crops should consider all the components of energy use sustainability, so that the developed policies and programs can cover all dimensions and take into account different aspects of energy use sustainability. As the results of this study can serve as a reference for other similar areas.